An Hα Cloud in the H I Tail: Recent Star Formation in the Outskirts of NGC 4258 Revealed by Nanshan 1 m Telescope - Cheng Cheng; Jia-Sheng Huang; Peng Wei; Ali Esamdin; Guojie Feng; Zhi-Xiang Zhang; Haojing Yan; Wei Du; Pei Zuo; Zijian Li; Gustavo Orellana-González; Letian Wang; et al. (The Astronomical Journal)
We present first-light deep H α imaging taken with the Nanshan 1 m wide-field telescope on the local galaxy NGC 4258, alongside archival data from Hubble Space telescope (HST), Westerbork Synthesis Radio Telescope, and The Dark Energy Camera Legacy Survey. The H α image shows ongoing star formation not only inside the galaxy but also in an H I cloud in the eastern H I tail, which is roughly 16 kpc away from the main galaxy. The HST images reveal several ultrablue compact objects (F555W − F814W < −0.5 mag,  FWHM ∼ 0 $\mathop{.}\limits^{\unicode{x02033}}$ 2) in the H α bright region, aligned with the H I tail, suggesting the presence of young open cluster candidate in the H I tail. Our results suggest that wide field H α imaging is a valuable tool for investigating recent star formation in the extended regions of NGC 4258. Furthermore, the star formation in diffuse H I tails could highlight an potential aspect of galaxy stellar halo formation, warranting further investigation of the impact of star formation in halos on galaxy evolution.